Mapeamento das competências dos gestores no processo de gestão de contratos terceirizados : o caso de uma Instituição Federal de Ensino Superior - Barros, Sandra Oliveira Mayer (Universidade Federal de São Carlos, 2015)
This research aims to conduct mapping of competencies in outsourced contract managers to identify competencies to the process of management of outsourced contracts in a Federal Institution of Higher Education (IFES).Therefore, historically it presents the characteristics of Public Management in Brazil; the definition and context of outsourcing, in addition to detailing the outsourced contract management process. The survey also points out the important competencies in performing outsourced contracts management process and performs the mapping of competencies in the study IFES, pointing out the training needs based on competencies. The research brings a case study in the research IFES. As data collection instruments are used documentary research, semi-structured interviews with managers to know the process of management of outsourced contracts and the application of questionnaires to identify gaps in competencies. The results provide an overview of the outsourced contract management process in the IFES study and mapping of individual competencies of outsourced contracts managers in IFES, allowing them to be identified training needs and competencies-based training How directions, the research shows the following requirements: adoption of specific training for outsourced contracts manager function, standardization of procedures and routines for the management of outsourced contracts in the institution; and creating a competency model for managers of outsourced service contracts.
Keywords: Administração pública; Terceirização; Contratos; Mapeamento de competências; Public administration; Outsourcing; Outsourced contract management; Competencies; Mapping competencies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO